EP1252 Magnetic resonance fingerprinting of cervical carcinoma- a feasibility study. (1st November 2019) - Lee, EYP; Perucho, JA; Cui, D; Hui, ESK
Abstract : Introduction/Background: Magnetic resonance imaging (MR) offers high soft tissue contrast to allow accurate assessment of local disease extent in cervical carcinoma. Magnetic resonance fingerprinting (MRF) is a new technique that allows simultaneous generation of multiple contrast with T1 and T2 quantitative maps. It has been shown to be useful in the grading of prostate carcinoma and detection of breast carcinoma. The aims of this study were to evaluate the feasibility of applying MRF in cervical carcinoma and quantifying the T1 and T2 values of tumour tissue. Methodology: Consecutive patients with newly diagnosed cervical carcinoma and MR examinations before treatment were prospectively recruited for MRF. MR examinations were performed on a 3T system (Philips Achieva TX). Multi-slice MRF was acquired using an inversion recovery steady-state free precession sequence with spiral-in-spiral-out trajectory, pseudorandomized flip angles and repetition times over 1000 dynamics. T1 and T2 maps were obtained using the MRF dictionary matching algorithm. Values were expressed as mean ± standard deviation. Results: Eleven patients (54.9 ± 16.8 years) with FIGO stage IB2 to IVA (IB2 1, IIA1 2, IIB 4, IIIC1 3, IVA 1) were recruited. All patients had squamous cell carcinoma, except for one with adenocarcinoma. The T1 value of tumour was 1534 ± 115 msec and the T2 value was 67 ± 12 msec. It was noted that the adenocarcinoma had higher T1 and T2 values (1721 msec and 93 msec) than squamous cell carcinoma (figures 1 and 2). Conclusion: Magnetic resonance fingerprinting was feasible in evaluation of cervical carcinoma and permitted T1 and T2 quantification of the tumour thereof with one acquisition. Disclosure: Nothing to disclose